Pentingnya Pengenalan Seks dalam Pencegahan Sexual Abuse Pada Anak Usia Dini - Maulana Muslich, Imroatun; Ni'mah, Mamluatun; Haflidlatil Kiromi, Ivonne (UIR PRESS, 2023)
The phenomenon of sexual deviation is starting to be found around us. Therefore the need for prevention and protection of early childhood. One of them starts by providing sex education guidance to children. But there are still many parents who underestimate the importance of sex education being taught from an early age. The purpose of providing sex education is to provide adequate understanding of the process of physical, mental, and emotional maturity and reduce fear and anxiety related to sexual adjustment and development. This study used a qualitative method with a literature study approach. The resulting data analysis is in the form of primary data from a book entitled